EFFECT OF LEFT VENTRICULAR SYSTOLIC DYSFUNCTION ON CEREBRAL HEMODYNAMICS IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION (THE RESULTS OF OBSERVATIONAL STUDIES) - V. E. Kulikov; M. Je. Hapman; P. A. Barov; M. A. Toneeva; V. A. Sergievskaja (Столичная издательская компания, 2015)
Aim. To study the effect of left ventricular (LV) systolic dysfunction on cerebral hemodynamic in patients with ST segment elevation myocardial infarction (STEMI) during acute period. Material and methods. Cerebral hemodynamics ultrasound assessment was performed in the extra-and intracranial vessels in 118 patients with STEMI. Results. Significant changes in cerebral hemodynamics were found in LV systolic dysfunction with ejection fraction (LVEF) ≤40% due to hemispheric blood flow asymmetry in the middle cerebral artery (MCA) as large as 45.1±6.7% with correlation coefficient r=-0.87. Compensation of cerebral blood flow was manifested in vasoconstriction or vasodilation (resistive index 0.63-0.76 and 0.49-0.43 c.u., respectively). Conclusion. A strong relationship between LV systolic dysfunction and cerebral hemodynamic was found in patients with STEMI. It was manifested in significant contralateral hemispheric blood flow asymmetry in MCA in patients with LVEF ≤40%. Reduction in cerebral blood flow velocity activated autoregulation mechanism in the form of vasoconstriction or vasodilation.